Pelatihan Guru PAUD Melalui Edukasi Seksual sebagai Upaya untuk Mencegah Kekerasan Seksual dan KDRT pada Anak Usia Dini - Indaria Tri Hariyani; Mira Pradipta Ariyanti; Siti Nur Fidatul Kusniyah (Universitas Negeri Gorontalo, 2026)
Schools are places of learning for students to gain knowledge. However, it is not unlikely that schools can also be fewer effective places for students to learn due to the weak ability of educators in educating about sexual violence in schools. The implementation of community service activities at TK Ananda Surabaya was motivated by the low knowledge of sexual violence and domestic violence among students. Therefore, it is hoped that this community service activity will train educational units and parents in an effort to minimize the prevention of sexual violence and domestic violence against students that occur in schools by providing training to PAUD teachers regarding sexual education to prevent sexual violence and domestic violence in early childhood in schools is also expected to create an effective and efficient learning atmosphere so that learning objectives will run smoothly to create a generation of the nation that is intelligent and has good morals. The activity was carried out from February-May 2026 with the involvement of 7 educators (1 principal and 6 teachers) and parents as accompanying participants. The methods used were training, socialization, mentoring, provision of educational media, and the establishment of a counseling room. Evaluation was carried out through observation and documentation. The results of the activities showed an increase in teachers' understanding of sexual education, the establishment of counseling rooms, the availability of sexual education media, and increased parental involvement in efforts to prevent sexual violence and domestic violence.